MANAJEMEN RANTAI PASOKAN PADA KEGIATAN KEWIRAUSAHAAN DAN INOVASI PRODUK SEBAGAI PENENTU KINERJA UKM - Satmoko, Nugroho Djati; Hersusetiyati, Hersusetiyati; Priadi, Muhammad Dadi; Yuniarsih, Yuyun (JISIP: Jurnal Ilmu Sosial dan Pendidikan, 2023)
The purpose of this study is to provide practical and theoretical insights into how small and medium enterprises (SMEs) adjust and further develop entrepreneurial activities, product innovation and SME business performance in the city of Bandung. This study used quantitative methods by using questionnaires for data collection. The number of samples used was 119 respondents using purposive sampling techniques. Partial least Square (PLS) is used for data processing. Based on the results of data analysis, it is implied that entrepreneurial competence has a significant effect on business performance, entrepreneurial competence has a significant effect on product innovation. However, product innovation does not have a significant effect on SME business performance.